Clinical presentations in presumed epidemic viral conjunctivitis: An observational study from a tertiary center in Eastern India - Loknath Mohanty; Anita Minj; Jyotirmayee Swain; Pradeep K Panigrahi; Sakshi Ahuja (TNOA Journal of Ophthalmic Science and Research, 2023)
Purpose: The present study aimed to investigate the current patterns of clinical presentation in the recent onset epidemic viral conjunctivitis in Eastern India. Methods: This hospital-based observational study was conducted from June 2023 to July 2023. All consecutive patients with presumed viral conjunctivitis were enrolled in the study. We performed a comprehensive ophthalmic evaluation to assess various signs and symptoms in every case. Data were statistically analyzed to study recent clinical patterns of viral conjunctivitis. Results: This study enrolled 2,640 patients with presumed viral conjunctivitis. The majority of the affected patients were males (59%). The mean age of the patients was 29.68 ± 15.84 years (range 6 months to 82 years). The highest number of cases (62.3%) was observed in patients aged more than 18 years. Most patients (62.7%) presented with symptoms in one eye, while 37.3% experienced symptoms in both eyes. Foreign body sensation and redness were the most common clinical presentations in 2,490 (94.38%) and 2,433 (92.1%) cases, respectively. Subconjunctival hemorrhage was seen in 47% of cases. Corneal involvement was noted in 43 (1.62%) cases. Resolution of symptoms was reported in most patients (84.4%) within a week. Conclusion: The current epidemic of viral conjunctivitis in Eastern India is self-limiting in nature with minimal corneal involvement. Early diagnosis, isolation of affected individuals, appropriate treatment, and adherence to personal hygiene practices are essential to curb the mass spread of conjunctivitis.